Terapi Audio Murotal Al-Qur’an terhadap Emosi Anak Autis - Abdulloh Azzahid; Muliadi Muliadi; Firman Rismanto (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
One of the characteristics of children with autism or Autism Spectrum Disorder (ASD) has emotional disorders. This is in accordance with what happened at SD Plus Al-Ghifari. By applying murottal Al-Qur’an therapy which is indirectly able to make children calmer in learning. This study aims to determine the process and effect of murottal Al-Qur’an therapy on emotional disturbances in autistic children. The study methods field research with three data collection techniques, namely observation, interviews, and documentation conducted at SD Plus Al-Ghifari Bandung. According to the helper at SD Plus Al-Ghifari after receiving the murottal Al-Qur’an treatment, the students were able to be calmer and able to follow the instructions from the helper. Al-Qur’an murottal therapy is able to affect emotional disturbances in children with ASD.